2020
DOI: 10.1080/15228916.2020.1838834
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Economic Growth in Uganda: A Multivariate Causal Linkage

Abstract: In this study, we have explored the dynamic causal relationship between financial development and economic growth in Uganda during the period from 1980 to 2015. Although the financegrowth nexus debate had been raging for decades, Uganda, just as many other low-income sub-Saharan African countries, has not yet received adequate coverage on the subject. To eliminate the variable-omission-bias associated with some previous studies, two intermittent variables namely, savings and inflation, have been included along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This is because economic growth according to the literature is a driver of FSD and financial inclusion. FSD and financial inclusion could also be drivers of economic growth (Park and Mercado, 2015; Suleiman and Abu-Qaun, 2008; Creane et al , 2003; Odhiambo, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because economic growth according to the literature is a driver of FSD and financial inclusion. FSD and financial inclusion could also be drivers of economic growth (Park and Mercado, 2015; Suleiman and Abu-Qaun, 2008; Creane et al , 2003; Odhiambo, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some empirical papers have analysed the effect of financial inclusion on economic growth together with income inequality and poverty alleviation (Park and Mercado, 2015). Other researchers have also investigated the link between economic growth and FSD (Levine, 1997; Tsuru, 2000; Suleiman and Abu-Qaun, 2008; Creane et al , 2003; Odhiambo, 2005). However, despite empirical findings supporting the positive impact of financial inclusion on growth and the effect of FSD on economic growth, there is a gap remaining in the literature regarding the tripartite relationship among financial inclusion, FSD and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…According to most empirical studies, financial sector development and financial inclusion are also found to be drivers of economic growth (Park and Mercado, 2015; Abu-Bader and Abu-Qarn, 2008; Creane et al , 2003; Odhiambo, 2005). Similarly, some empirical papers have also examined the impact of financial inclusion on poverty reduction, economic growth, income inequality, monetary policy and financial sector development (Anarfo et al , 2019a; Anarfo et al , 2019b; Brune et al , 2011; Burgess and Pande, 2005; Park and Mercado, 2015; Honohan, 2008; Rojas-Suarez, 2010; Thorat, 2006; Chibba, 2009; Dabla-Norris et al , 2015; Kpodar and Andrianaivo, 2011; Johal, 2016; Sharma, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, some empirical papers have also examined the impact of financial inclusion on poverty reduction, economic growth, income inequality, monetary policy and financial sector development (Anarfo et al , 2019a; Anarfo et al , 2019b; Brune et al , 2011; Burgess and Pande, 2005; Park and Mercado, 2015; Honohan, 2008; Rojas-Suarez, 2010; Thorat, 2006; Chibba, 2009; Dabla-Norris et al , 2015; Kpodar and Andrianaivo, 2011; Johal, 2016; Sharma, 2016). Other researchers have also examined the link between financial sector development and economic growth (Levine, 1997; Abu-Bader and Abu-Qarn, 2008; Creane et al , 2003; Odhiambo, 2005). Thus, the bi-causal linkages among financial inclusion, remittances, economic growth and financial sector development appear to have eluded the thought of researchers, and this has resulted in a limited understanding of the relationship among these variables.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation